2012
DOI: 10.5539/elt.v5n3p62
|View full text |Cite
|
Sign up to set email alerts
|

Non-empirically Based Teaching Materials Can be Positively Misleading: A Case of Modal Auxiliary Verbs in Malaysian English Language Textbooks

Abstract: Using corpus approach, a growing number of researchers blamed textbooks for neglecting important information on the use of grammatical structures in natural English. Likewise, the prescribed Malaysian English textbooks used in schools are reportedly prepared through a process of material development that involves intuition. Hence, a corpus-based study with the population that was sourced from five Malaysian English language textbooks (Forms 1-5) was adopted to identify modal auxiliary verbs' order and ranking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the inclusion of authentic texts such as horoscopes can supplement the existing Malaysian textbooks. As corpus studies of Malaysian textbooks found no implicit teaching of modals would, could and shall in the entire lower secondary level (Mukundan & Khojasteh, 2011;Khojasteh & Kafipour, 2012), various examples found in horoscope entries could reinforce students' learning of the forms and functions of modal auxiliary verbs. The concordance lines generated from concordance could be used to show students the appropriate use of modal auxiliary verbs in real-life context.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the inclusion of authentic texts such as horoscopes can supplement the existing Malaysian textbooks. As corpus studies of Malaysian textbooks found no implicit teaching of modals would, could and shall in the entire lower secondary level (Mukundan & Khojasteh, 2011;Khojasteh & Kafipour, 2012), various examples found in horoscope entries could reinforce students' learning of the forms and functions of modal auxiliary verbs. The concordance lines generated from concordance could be used to show students the appropriate use of modal auxiliary verbs in real-life context.…”
Section: Discussionmentioning
confidence: 93%
“…A programming language-valued triangular fuzzy ARAS approach can use such records to rank options and/or examine distinct eventualities. Therefore, by way of the use of this approach, choice makers are given the possibility to express their constructive, pessimistic and realistic attitudes [4]. Fuzzy ARAS methods and Chief Accounting Officers Ambiguous to evaluate A weighted product model.…”
Section: Fuzzy Arasmentioning
confidence: 99%
“…The first organization includes the modal verb can and its past shape can, which are specially utilized in English to express capability, permission, and opportunity. The second organization specifically includes other modal auxiliary verbs used to suggest obligation or requirement (must, want to, have to, ought to, need to), permission or possibility (can also add, might), and intention, prediction, or threat (may want to) [13]. Sample auxiliary verbs (along with their bad forms) found in 5 In lower and upper levels English textbooks in descending order Given: can, will, need to, May it, Mucht, May it Also, Gold, May and Sal The textbook corpus contained a complete of 4154 key samples.…”
Section: Introductionmentioning
confidence: 99%